New paleontological and biostratigraphical data (calcareous nannofossils, ostracods, brachiopods), correlations and lithostratigraphic units in the Urgonian facies (latest Hauterivian-Barremian) of the Swiss and French Jura Mountains: the Falaises Member and the Saars Formation (former “Gorges de l’Orbe Formation”) - Pierre‑Olivier Mojon; Eric De Kaenel (Swiss Journal of Geosciences)
Abstract From latest Hauterivian to latest Barremian, the Urgonian facies of the Swiss and French Jura Mountains are subdivided into three formations and five members: new Saars Formation (= former “Gorges de l’Orbe Formation” sensu Strasser et al., 2016; Pictet, 2021) with a new Falaises Member below the Montcherand and Bôle members of Pictet (2021), Rocher des Hirondelles Formation with Fort de l’Ecluse and Rivière members (Pictet, 2021, revised), and Vallorbe Formation (revised from Strasser et al., 2016 and the “Vallorbe Member” of Pictet, 2021). The latest Hauterivian-early Late Barremien Saars Formation includes three members 1) to 3): 1) Latest Hauterivian-Early Barremian Falaises Member with new Early Barremian nannoflora from the Corcelles Marls (much younger than the late Early Hauterivian nannoflora from the Uttins Marls of the type locality at Mont de Chamblon), primitive orbitolinids Praedictyorbitolina claveli Schroeder, 1994; and fossils/microfossils usually considered as Hauterivian markers: echinids Pseudholaster intermedius (Münster in Goldfuss, 1826), brachiopods Glosseudesia semistriata (Defrance, 1828), Lamellaerynchia hauteriviensis Burri, 1953 and Plicarostrum aubersonense Burri, 1956, and ostracods of the Assemblage 1 [Protocythere triplicata (Roemer, 1841), Rehacythereis bernardi (Grosdidier, 1964), Schuleridea clunicularis (Triebel, 1938), Schuleridea gr. thoerenensis (Triebel, 1938)]. 2) Early Barremian Montcherand Member with brachiopods Glosseudesia inexpectata Mojon, n. sp. and Glosseudesia ebrodunensis (de Loriol, 1864), and ostracods of the Assemblage 2 [Strigosocythere strigosa (Grosdidier, 1964), P. triplicata, and juvenile immature species markers of the next ostracod Assemblage 3]. 3) Early to early Late Barremian Bôle Member with adult ostracod markers of the Assemblage 3 [Rehacythereis geometrica (Damotte and Grosdidier, 1963), Bairdoppilata barremiana Mojon, n. sp., Bairdoppilata luminosa Kuznetsova, 1961; Neocythere (Centrocythere) gottisi Damotte and Grosdidier, 1963; Schuleridea derooi Damotte and Grosdidier, 1963; Schuleridea alata Kaye, 1965; Dolocytheridea intermedia Oertli, 1958]. 4) The Early to Late Barremian Fort de l’Ecluse Member/Rocher des Hirondelles Formation and Late Barremian Rivière Member/Vallorbe Formation are characterized by markers such as echinids Heteraster couloni (L. Agassiz, 1839), orbitolinids [Praedictyorbitolina carthusiana Schoeder et al., 1990; Eopalorbitolina charollaisi Schroeder and Conrad, 1967; Valserina broennimanni Schroeder and Conrad, 1967; Paleodictyoconus actinostoma Arnaud-Vanneau and Schroeder, 1976; Paracoskinolina maynci (Chevalier, 1961)], and typical ostracods of the Assemblage 4 [Strigosocythere chalilovi (Kuznetsova, 1961), Rehacythereis buechlerae (Oertli, 1958) only in the southern Jura and replaced by R. geometrica in the central Jura, Platycythereis rostrata Sauvagnat, 1999] extended in the latest Barremian-Early Aptian Fulie Member of the basal Perte-du-Rhône Formation defined by Pictet et al. (2016). ZooBank LSID: urn:lsid:zoobank.org:pub:9CDFC0BE-DAD2-47E8-A213-7AE74A923350